2018
DOI: 10.1186/s41065-018-0076-2
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Neanderthal BRCA2 gene might be related to their distinctive cognitive profile

Abstract: The unique divergence of the BRCA2 gene in Neanderthals compared to modern humans has been hypothesized to account for a differential susceptibility to cancer. However, the role of the gene in brain development and its connection with autism suggest that these differences might be (also) related to the more encapsulated nature of the Neanderthal cognition and their (inferred) autistic-like features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Our results have similarity with other studies conducted previously. Several studies investigated the association of DNA repair, genotoxic, and environmental factors and autism and found some DNA repair-related genes known to be associated with autism spectrum phenotype, such as OGG1, BRCA2, FAN1, MBD4, MUTYH , and XRCC4 ( Li et al, 2005 , Sajdel-Sulkowska et al, 2009 , Cukier et al, 2010 , Ionita-Laza et al, 2014 , Shpyleva et al, 2014 , 2016, Markkanen et al, 2016 , Benitez-Burraco, 2018 ). Muraleedharan et al examined DNA damage and DNA repair efficiency in schizophrenia using the Comet assay, and their results showed significant differences between study groups ( Muraleedharan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results have similarity with other studies conducted previously. Several studies investigated the association of DNA repair, genotoxic, and environmental factors and autism and found some DNA repair-related genes known to be associated with autism spectrum phenotype, such as OGG1, BRCA2, FAN1, MBD4, MUTYH , and XRCC4 ( Li et al, 2005 , Sajdel-Sulkowska et al, 2009 , Cukier et al, 2010 , Ionita-Laza et al, 2014 , Shpyleva et al, 2014 , 2016, Markkanen et al, 2016 , Benitez-Burraco, 2018 ). Muraleedharan et al examined DNA damage and DNA repair efficiency in schizophrenia using the Comet assay, and their results showed significant differences between study groups ( Muraleedharan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…BRCA2 is another gene involved in maintaining the stability of the genome, especially in the repair of double-strand breaks through the homologous recombination pathway. Studies have shown mutations in this gene are related to autism phenotypes ( Neale et al, 2012 , Benitez-Burraco, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the deletion (chromosomal rearrangement corresponding to the loss of a DNA fragment that can range from a single base pair to a large fragment of chromosomes) 16p11.2 is linked to Homo desinovensis and autism (Tabet et al, 2012). Thus, Benítez-Burraco (2018) explains that connection between Neanderthal genome and autism suggests that these differences could be related to the more encapsulated nature of Neanderthal cognition and their autistic-like characteristics. Also, Polimanti & Gelernter (2017) made the hypothesis that "certain ASD risk alleles were under positive selection during human evolution due to their involvement in neurogenesis and cognitive ability" (p. 1).…”
Section: Iii) Creativity Autism and Neurodevelopmental Disordersmentioning
confidence: 99%
“…In 2019, an estimated 55.2 million people worldwide suffer from dementia and 1.6 million die from it, making it to be the seventh leading cause of death, which brings a serious global health burden[2]. Currently, dozens of genes associated with cognition have been identified, including APOE[3], MEF2[4], COMT[5], KMO[6], BRCA2[7], etc., leading to advances in the treatment of cognitive disorders. However, due to the complexity of cognitive dysfunction, the role of common genetic variants and the pathogenic mechanisms have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, dozens of genes associated with cognition have been identified, including APOE [3], MEF2 [4], COMT [5], KMO [6], BRCA2 [7], etc., leading to advances in the treatment of cognitive disorders. However, due to the complexity of cognitive dysfunction, the role of common genetic variants and the pathogenic mechanisms have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%